2005
DOI: 10.2320/matertrans.46.2253
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Permeability in Nb–Ti–Ni Alloys Containing Much Primary (Nb,Ti) Phase

Abstract: In order to develop high hydrogen permeability alloys, structural changes induced by hydrogenation, microstructures and hydrogen permeability È were investigated for samples on the straight line connecting the eutectic and the primary phase in the Nb-Ti-Ni phase diagram. È was measurable in the alloys containing much amount of the eutectic phase, indicating that the eutectic microstructure suppresses the hydrogen embrittlement. The value of È increased with increasing Nb content and the volume fraction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…2(a) and (d)), again indicating the importance of aligning Nb rods so as to penetrate the thickness of the membrane. The largest value of hydrogen permeability obtained at 673 K for the perpendicular configuration specimen grown at 1.0 mm/h is as high as 2.60 Â 10 À8 mol H 2 m À1 s À1 Pa À1/2 , which is more than twice that reported for the as-cast Nbe40Nie40Ti eutectic alloy and is comparable to that reported for the NbeNiTi alloys consisting of grains of the primary Nb phase and those of the eutectic [11]. Of importance to note is that no cracks are observed after hydrogen permeability measurements for all the specimens investigated, indicating that the directionally solidified alloys with the aligned NbeNiTi eutectic microstructure is not susceptible to hydrogen embrittlement at all during hydrogen permeation.…”
Section: Hydrogen Permeabilitysupporting
confidence: 81%
“…2(a) and (d)), again indicating the importance of aligning Nb rods so as to penetrate the thickness of the membrane. The largest value of hydrogen permeability obtained at 673 K for the perpendicular configuration specimen grown at 1.0 mm/h is as high as 2.60 Â 10 À8 mol H 2 m À1 s À1 Pa À1/2 , which is more than twice that reported for the as-cast Nbe40Nie40Ti eutectic alloy and is comparable to that reported for the NbeNiTi alloys consisting of grains of the primary Nb phase and those of the eutectic [11]. Of importance to note is that no cracks are observed after hydrogen permeability measurements for all the specimens investigated, indicating that the directionally solidified alloys with the aligned NbeNiTi eutectic microstructure is not susceptible to hydrogen embrittlement at all during hydrogen permeation.…”
Section: Hydrogen Permeabilitysupporting
confidence: 81%
“…Especially, the alloys indicated by double circles show a higher rolling reduction rate (higher than 80%). We can see that the alloys showing high r u values locate near the line connecting the compositions of Ti 50 Ni 50 and Nb 85 Ti 15 , which corresponds to the line connecting the eutectic and the primary phases [10]. As an example, an XRD pattern of the as-cast Nb 40 Ti 30 Ni 30 alloy, which shows 80% or more rolling reduction rate, is shown in Fig.…”
Section: Ultimate Rolling Reduction Rate Of the Nb-tini Alloysmentioning
confidence: 94%
“…These Nb-TiNi alloys consist of the primary (Nb, Ti) and the eutectic {(Nb, Ti) þ TiNi} phases. It has been reported that the former phase contributes mainly to hydrogen permeation, while the latter one mainly suppresses the hydrogen embrittlement [10,11]. However, it is uncertain whether the thin membrane can be fabricated by rolling and subsequent anneal of these NbTiNi alloys.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that hydrogen permeation in the Nb-TiNi alloys is mainly determined by the primary phase. 15) Then, the main reason for the increment of È with increasing Ti/Ni ratio is considered to be the increase of the volume fraction of the primary phase. Chemical compositions of the primary phases vary widely and complicatedly as shown in Table 1, but we can notice the following tendency.…”
Section: Methodsmentioning
confidence: 99%